Jurisdiction and Security - Erin Gibbs Van Brunschot (The Journal of Intelligence, Conflict and Warfare, 2022)
On June 16, 2022, the Canadian Association for Security and Intelligence Studies (CASIS)-Vancouver hosted a Digital Roundtable titled Jurisdiction and Security, conducted by Dr. Erin Gibbs Van Brunschot, a Professor of Sociology and the Director of the Centre for Military, Security and Strategic Studies (CMSS) at the University of Calgary. The presentation was followed by a question-and-answer period with questions from the audience and CASIS-Vancouver executives. The discussion topics centred around the jurisdictional challenges that limit security responses to Canadian national security threats and how security networks must be established to tackle these evolving threats.